Post-Jungian perspectives on archetypes of individuation in Aldous Huxley’s Brave new world and Island - Bessa, Maria de Fátima de Castro (Em Tese, 2008)
The archetypes of individuation, as proposed by C. G. Jung, have been challenged by post-Jungian writers. Persona, shadow, anima and self offer examples of these new approaches, and their use in the analysis of Aldous Huxley’s Brave New World and Island highlight some cultural aspects of the novels.